Lower paleolithic site Kremenac near the village Rujnik (Serbia) - Šarić Josip (Starinar, 2011)
The site Kremenac has been known for decades as a location where large quantity of raw material for production of the chipped stone artifacts had been found. Only the excavations in 1995 and 1996 defined to a certain extent the artifacts, which indicated by their morphology the Lower Paleolithic date of this site. Because of the impossibility to study for the time being the material from the excavations this work deals with the surface chance finds, which are typologically and even more morphologically distinctive and on the basis of which it is possible to indicate the exceptional early date and importance of this site. [Projekat Ministarstva nauke Republike Srbije, br. 177020: Archaeology of Serbia: Cultural identity, integrational factors, technological processes and role of Central Balkan in evolution of European prehistory]